ANALISIS PERENCANAAN DAN PENGEMBANGAN KARIER BINTARA POLRI SATUAN BRIGADE MOBIL DAERAH JAWA BARAT (STUDI KASUS PADA BATALYON A PELOPOR) - Cecep Suarha; Ginanjar Wira Saputra; Ahmad Johan (Halu Oleo University, 2023)
The purpose of this study was to determine career planning and career development. The research method used in this study is a descriptive research method with a qualitative approach. The data collection techniques used in this study are observation, interviews, research instruments and documentation. The research results show that planning analysis and career development in the form of promotions and accelerated ranks of Battalion A Pioneer personnel in general have been carried out well in accordance with the established plans or regulations, especially regarding the criteria for personnel violations both in disciplinary hearings, codes of ethics and criminal acts. weaknesses in supervision from the level of leadership to subordinates. The conclusion of this study is that the policies of the leadership regarding career planning and development in the form of promotions and accelerated ranks for Battalion A Pioneer personnel have had the expected impact, especially to improve the discipline and performance of Battalion A Pioneer personnel with regard to attendance levels, main tasks and functions as well as personnel work behavior.